Tantangan dan Peluang Pendidikan Agama Islam di Era Society 5.0 - Yemmardotillah, M.; Indria, Anita; Asrizallis; Indriani, Rini (Yayasan Dharma Lentera Khatulistiwa (MALEWA), 2024)
The Society 5.0 era, characterized by the integration of advanced technology in daily life, brings significant challenges and opportunities for Islamic religious education. This research aims to explore the dynamics of Islamic education in the context of digital transformation, identify key challenges, and analyze potential opportunities and adaptation strategies. Using a comprehensive literature review approach and thematic analysis, this research highlights major challenges such as limited technological infrastructure in Islamic educational institutions, the digital divide between educators and students, data security and privacy issues, and the potential reduction in open interaction and communal values. However, this era also opens significant opportunities, including increased accessibility to Islamic education through digital platforms, learning personalization using AI, development of Open Educational Resources (OER), and global collaboration among Islamic educational institutions. To address these challenges and capitalize on the opportunities, this research proposes adaptation strategies including curriculum development that integrates digital literacy with Islamic values, continuous training for educators, implementation of blended learning models, and development of specialized e-learning platforms for Islamic religious education. The research findings highlight the importance of a balanced approach in adopting technology, maintaining the spiritual essence of Islamic education while leveraging digital innovations. The implications of these findings are crucial for education policymakers, Islamic Educational Institutions, and education practitioners in designing effective and innovative strategies for Islamic religious education in the Society 5.0 era. This is an open access article under the CC-BY-SA license